IC- TAP infection control- training and policies for hospitals - Philpott- Howard, J.; Casewell, M.; Desai, N. (London : W.B. Saunders, 1998)
(Producer) Provides access to information on infections and key hospital infection control policies and procedures. Features individual information sheets on particular infections that can be printed out, helpful pop-up glossaries for defining words, a six-step handwash simulation, and full text searching ability.
CD is available at Koleksi Media Perpustakaan HUKM
System requirements: 80486 multimedia PC/33mHz, or higher recommended; 8MB RAM (12MB or more recommended), 20MB free hard disk space; Microsoft Windows 3.1 or higher; VGA col. monitor (capable of displaying at least 256 colours at 640x480 pixel resolution); CD-ROM drive; Windows compatible mouse or other pointing device.
Keywords: Cross Infection -- prevention and control -- CD-ROM